Decoding the internesting movements of marine turtles using a fine-scale behavioral state approach - Santos, Armando J. B.; Cullen, Joshua; Vieira, Daniel H. G.; Lima, Eduardo H. S. M.; Quennessen, Victoria; Santos, Erik A. P. dos; Bellini, Claudio; Ramos, Renata; Fuentes, Mariana M. P. B. (Frontiers in Ecology and Evolution, 2023)
An understanding of animal behavior is critical to determine their ecological role and to inform conservation efforts. However, observing hidden behaviors can be challenging, especially for animals that spend most of their time underwater. Animal-borne devices are valuable tools to estimate hidden behavioral states. In this study, we investigated the fine-scale behavior of internesting hawksbill turtles using the mixed-membership method for movement (M4) to integrate dive variables with spatial components, identifying five latent behavioral states: 1) pre-nesting, 2) transit, 3) quiescence, and 4) area restricted search within and 5) near the residence of turtles. The last three states, associated with a residency period, showed lower activity levels. Notably, when compared to other behaviors the pre-nesting exhibited shallower and remarkably long dives of up to 292 minutes. We noted high fidelity to residence core areas and nesting beaches, within and between nesting seasons, with residence areas contracting within a season. These results offer the most detailed breakdown of turtle movement behaviors during the internesting to date, providing valuable insights into their ecology and behavior. This information can inform marine turtle conservation and management efforts since utilization distributions of individual behavioral states can be used to determine the specific susceptibility of turtles spatially to various threats based on their behavior. The analyses of utilization distribution revealed a minimal overlap with existing marine protected areas (0.4%), and we show how a new proposal would expand protection to 30%. In short, this study provides valuable guidance for conservation and management of internesting marine turtles at a fine spatiotemporal resolution and can be used to enhance national action plans for endangered species, including the expansion of existing Marine Protected Areas. By flexibly incorporating biologically informative parameters, this approach can be used to study behavior outside of the hawksbill breeding season or even beyond this species.